Anterolateral thigh flap for upper extremity reconstruction in older patients. Issue 8 (5th October 2022) - Ikeguchi, Ryosuke; Noguchi, Takashi; Ando, Maki; Yoshimoto, Koichi; Sakamoto, Daichi; Matsuda, Shuichi
Abstract: Background: The anterolateral thigh (ALT) flap has been used in upper extremity reconstruction. However, there is no consensus about the age at which the flap can be used safely, which is a concern when applying ALT flaps for upper extremity reconstruction in older patients. We present the results of the use of ALT flap for upper extremity reconstruction in a series of older patients. Patients and methods: Seventeen patients who underwent ALT flaps for soft tissue defects in the upper extremities from 2010 to 2020 were included. The patients' mean age was 63.5 (range, 26–83) years. Ten of seventeen patients were smokers. Defect locations were the dorsum of the hand in seven patients, palm in two patients, dorsum and palm in two patients, and forearm in six patients. Etiologies of the defect were traumatic in 14 patients and malignant tumor in three patients. The defect size was 8 to 25 × 5 to 11 cm. When dissecting the perforators, we preserved the surrounding small muscular and fatty tissue with the perforators and to harvest them together to prevent intima damage. Flap thinning was performed for 16 flaps to adjust the flap thickness to match defect site requirements. We used an end‐to‐side or interposition arterial anastomosis to regulate the blood flow. Results: The flap size was 9 to 28 × 5 to 13 cm. One patient had venous congestion and vein re‐anastomosis was needed. All flaps survived. One patient had a methicillin‐resistant Staphylococcus aureus infection and debridement and irrigation was needed. The mean follow‐up period was 20 (range, 13–37) months. Fifteen patients returned their previous activities. The mean DASH score was 30.6 (range, 3–70). Conclusions: Regardless of patient age or smoking status, the ALT flap was a safe and reliable surgical option for soft tissue defect reconstruction of the upper extremity.